The Engineered Child: Bioethics, Exploitation, and the Commodification of Orphaned Bodies in The Lost Children of Paradise: https://doi.org/10.5281/zenodo.17179101 - Nayab Amjad; Rahat Bashir (`, 2025)
This paper examines the ontological, ethical, and political implications of biotechnologically altered orphans in The Lost Children of Paradise using Donn Haraway's cyborg theory and Michel Foucault's idea of biopower as critical frameworks. The story of The Lost Children of Paradise exposes the industrialization of vulnerable children whose lives are determined by institutional function rather than care, orphan bodies as set in dystopian societies, viewed as raw material for technological growth and exploitation. These children are now viewed as set-up objects rather than independent beings, created for work, warfare, and surveillance, and utilized as tools of systematic exploitation. According to Foucault's theory of biopolitics, the orphaned children are becoming an object of optimization and regulation as a result of the way power operates on and through life itself. The conventional divisions between machine and human, children and instruments, and nature and technological advancement are all challenged by Haraway's cyborg theory. These children's hybrid existence redefines what it means to be "child" in a world governed by techno-scientific ideology, questioning humanistic ideas of innocence, reliance, and biological authenticity. This paper adopts qualitative research to examine how less fortunate bodies, especially those of orphan children, are subjected to both negligence and excessive control in the name of advancement. It critiques the unethical quest for human growth as well as the destructive tendencies of late capitalist biopolitics. Using close textual reading, the study explores the major ethical issues such s exploitation of life, the removal of identity under systems of control, and the lack of approval in child engineering. By portraying the designed children as both a product and a potential agent of resistance, the novel encourages the reader to reconsider the present debates about identity, engineering, and the future of human agency. Through the analysis of this novel, it becomes an important place to examine how bodies, particularly those of the orphaned, are formed, controlled, and eventually used for profit under systems of political and scientific dominance. Keywords: Engineered children, Bioethics, Commodification of orphaned bodies, Biopolitics, Child exploitation